Empowering Users to Respond to Misinformation about Covid-19 - Vraga, Emily K. (2020)
The World Health Organization has declared that misinformation shared on social media about Covid-19 is an “infodemic” that must be fought alongside the pandemic itself. We reflect on how news literacy and science literacy can provide a foundation to combat misinformation about Covid-19 by giving social media users the tools to identify, consume, and share high-quality information. These skills can be put into practice to combat the infodemic by amplifying quality information and actively correcting misinformation seen on social media. We conclude by considering the extent to which what we know about these literacies and related behaviors can be extended to less-researched areas like the Global South.